2018
DOI: 10.1002/gps.4999
|View full text |Cite
|
Sign up to set email alerts
|

Prescription opioid and benzodiazepine misuse is associated with suicidal ideation in older adults

Abstract: Objectives: Suicide in older adults is a major public health issue. Past research across the US adult population has linked prescription medication misuse with suicidal ideation. No work has evaluated associations between prescription opioid or benzodiazepine misuse and suicidal ideation in older adults, and this work aimed to address that gap. Methods/Design: Data were from adults 50 years and older participating in the 2015-16 National Survey on Drug Use and Health (n = 17,608). Design-based logistic regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
45
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 49 publications
0
45
1
Order By: Relevance
“…Other substance dependence or abuse has been associated with opioid misuse based on various risk factors. [11,25,30,45,52] In this study, we found that nicotine [25,26], alcohol [25,27], cocaine [52], methamphetamine [29], tranquilizers [31,32,53], other illicit stimulants [15], and marijuana [25] have a positive relationship with opioid misuse and use disorder. The stimulant effect from nicotine, cocaine, methamphetamine, and other illicit stimulants may mitigate the depressive effects of opioids and may increase the "high" effect.…”
Section: Discussionmentioning
confidence: 61%
“…Other substance dependence or abuse has been associated with opioid misuse based on various risk factors. [11,25,30,45,52] In this study, we found that nicotine [25,26], alcohol [25,27], cocaine [52], methamphetamine [29], tranquilizers [31,32,53], other illicit stimulants [15], and marijuana [25] have a positive relationship with opioid misuse and use disorder. The stimulant effect from nicotine, cocaine, methamphetamine, and other illicit stimulants may mitigate the depressive effects of opioids and may increase the "high" effect.…”
Section: Discussionmentioning
confidence: 61%
“…Other substance dependence or abuse has been associated with opioid misuse based on varying risk factors. [13,28,33,47,50] In this study, we speci cally found that nicotine, [28,29] alcohol, [28,30] cocaine, [50] methamphetamine, [32] tranquilizers, [34,35,51] other illicit stimulants [20], and marijuana [28] have a positive relationship with opioid misuse and use disorder. The stimulant effect from nicotine, cocaine, methamphetamine, and other illicit stimulants have been stipulated to mitigate the depressive effects of opioids and may increase the "high" effect.…”
Section: Discussionmentioning
confidence: 64%
“…When combined with the elevated rates of past-year opioid misuse in older adults using "physician sources only", though, reason for concern emerges. Previous work suggests that opioid and benzodiazepine misuse are each associated with an increased likelihood of suicidal ideation in older adults (Schepis, Simoni-Wastila, & McCabe, 2019). The high rates of older adult sedative/tranquilizer exposure (Maree et al, 2016) and significant misuserelated consequences indicate a need for careful screening and monitoring of older adults prescribed tranquilizer/sedative medications, as they may be more likely to experience suicidality and misuse opioid medication.…”
Section: Discussionmentioning
confidence: 99%